2023
DOI: 10.17977/um018v6i22023p145-156
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Students’ Academic Performance at the Federal College of Education Asaba Nigeria: Mining Education Data

Arnold Adimabua Ojugoa,
Christopher Chukwufunaya Odiakaose,
Frances Emordi
et al.

Abstract: One main objective of higher education is to provide quality education to its students. One way to achieve the highest level of quality in the higher education system is by discovering knowledge for prediction regarding enrolment of students in a particular course, alienation of traditional classroom teaching model, detection of unfair means used in online examination, detection of abnormal values in the result sheets of the students, and prediction about students’ performance. The knowledge is hidden among th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…It thus uses portfolios of smart-contract policies to drive the value chain framework [70]- [72] to satisfy all stakeholder needs and requirements therein [73]. Furthermore, a value-chain manager must consider the interactions of both (un)known parameters, relations in their limitations as well as minor shifts from which they must yield alternatives that will provide effective results to the value chain [74]- [76].…”
Section: Blockchain Technology and Adoptionmentioning
confidence: 99%
“…It thus uses portfolios of smart-contract policies to drive the value chain framework [70]- [72] to satisfy all stakeholder needs and requirements therein [73]. Furthermore, a value-chain manager must consider the interactions of both (un)known parameters, relations in their limitations as well as minor shifts from which they must yield alternatives that will provide effective results to the value chain [74]- [76].…”
Section: Blockchain Technology and Adoptionmentioning
confidence: 99%
“…But, a consequent effect of such interaction, integration, advances and migration activities [2] is the relative ease in acceleration and propagation of infectious disease [3], and its consequent spread evolution from an epidemic to a pandemic [4]. It became globally clear, that covid-19 pandemic witnessed: (a) closure of schools [5]- [7] with limited public gathering in our society [8], (b) adoption of social distancing as means to curb its propagation effects [9]- [11], (c) residents' migration pattern [12]- [14], (d) responses to businesses birthing remote-work with its reduce monetization [15]- [17], and (e) the adoption of nose-masks in public places and especially in schools [18]- [20]. Post-covid-19 reports have revealed that: (a) traditional schools were shut down to curb its widespread propagation, (b) businesses were impacted globally, (c) the short-term disruptions in businesses yielded great significant negative impacts, and (d) such impacts if mishandled -may yield long-term effects that ripple throughout the society with the formation of new businesses as well as sustenance of older businesses [21]- [23].…”
Section: Introductionmentioning
confidence: 99%